Effect of ulinastatin on oxidative stress and intestinal flora in rats with sepsis-induced acute lung injury - ZHANG Yiren*, CHEN Mengxiao, LI Xiang, YU Xiangyou, WANG Yi (Zhongguo linchuang yanjiu)
Objective To investigate the effect of ulinastatin (UTI) on the level of oxidative stress as well as intestinal flora in rats with sepsis-induced acute lung injury (ALI), providing theoretical support for the diagnosis and treatment of sepsis-induced ALI. Methods Eighteen male Wistar rats were divided into three groups: sham operation group (Sham group), cecum ligation and puncture (CLP) induced sepsis group (CLP group), and sepsis+UTI intervention group (CLP+UTI group, intraperitoneal injection of 100 kU/kg UTI instantly after CLP), with 6 rats in each group. Lung tissues were obtained from rats executed 24 hours after modeling, and pathological changes were observed under the light microscope. Superoxide dismutase (SOD) activity and malondialdehyde (MDA) content were detected by enzyme linked immunosorbent assay (ELISA). The expression of nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) was measured by western blotting. The mRNA expression of Nrf2, HO-1, tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) was detected by real-time quantitative polymerase chain reaction (RT-qPCR). The changes of intestinal flora in rats were detected by 16S rRNA gene sequencing. Results Compared with the Sham group, histopathologic analysis observed that the lungs of the CLP group exhibited alveolar effusion, inflammatory cell infiltration, and structural disorganization; the mRNA expression of TNF-α and IL-6 were significantly elevated in lung tissue, SOD activity decreased, the content of MDA increased; the mRNA and protein expressions of Nrf2 and HO-1 in lung tissue were decreased. Compared with the CLP group, the lung tissue damage in the CLP+UTI group was significantly relieved, the mRNA expression of TNF-α and IL-6 were significantly decreased in lung tissue (P＜0.05), SOD activity increased ［SOD (U/mg prot): 11.83±0.99 vs 6.74±0.43, P＜0.05］, the content of MDA decreased ［MDA (nmol/mg prot): 0.16±0.04 vs 0.38±0.03, P＜0.05］; the mRNA and protein expressions of Nrf2 and HO-1 in lung tissue were increased (P＜0.05). Conclusion UTI has a significant protective effect against sepsis-induced ALI, possibly by modulating the intestinal flora which in turn ameliorates inflammatory injury and reduces oxidative stress injury.